2013
DOI: 10.7448/ias.16.1.18567
|View full text |Cite
|
Sign up to set email alerts
|

Non‐nucleoside reverse transcriptase inhibitors: a review on pharmacokinetics, pharmacodynamics, safety and tolerability

Abstract: IntroductionHuman immunodeficiency virus (HIV) type-1 non-nucleoside and nucleoside reverse transcriptase inhibitors (NNRTIs) are key drugs of highly active antiretroviral therapy (HAART) in the clinical management of acquired immune deficiency syndrome (AIDS)/HIV infection.DiscussionFirst-generation NNRTIs, nevirapine (NVP), delavirdine (DLV) and efavirenz (EFV) are drugs with a low genetic barrier and poor resistance profile, which has led to the development of new generations of NNRTIs. Second-generation NN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
251
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(261 citation statements)
references
References 86 publications
8
251
2
Order By: Relevance
“…Molesworth et al found a sensitivity of 99% comparing third-generation RDT kits with third-generation EIA during HIV testing in the context of a household survey, using initially two RDTs in parallel with a tiebreaker, then two RDTs in series with a tiebreaker and finally retesting all positives and 10% of the negatives in the laboratory [22]. Jackson et al found a sensitivity of 98% in a community randomized controlled trial of home-based HCT conducted by lay counsellors again comparing third-generation RDT kits with a third-generation EIA [23]. Wolpaw et al found an RDT sensitivity of 68.7% which improved to 93.5% following switching test kit brands and to 98% following implementation of quality improvement measures upon retesting individuals who previously tested HIV negative at primary care clinics in Cape Town, South Africa [24].…”
Section: Discussionmentioning
confidence: 99%
“…Molesworth et al found a sensitivity of 99% comparing third-generation RDT kits with third-generation EIA during HIV testing in the context of a household survey, using initially two RDTs in parallel with a tiebreaker, then two RDTs in series with a tiebreaker and finally retesting all positives and 10% of the negatives in the laboratory [22]. Jackson et al found a sensitivity of 98% in a community randomized controlled trial of home-based HCT conducted by lay counsellors again comparing third-generation RDT kits with a third-generation EIA [23]. Wolpaw et al found an RDT sensitivity of 68.7% which improved to 93.5% following switching test kit brands and to 98% following implementation of quality improvement measures upon retesting individuals who previously tested HIV negative at primary care clinics in Cape Town, South Africa [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rates of disease progression, opportunistic infections, and mortality decreased with the implementation of HAART, and the combination of anti-HIV drugs resulted in longer survival and a better quality of life for the people infected with the virus (Colombo et al, 2014). The most common drug treatment administered to patients consists of two nucleoside reverse transcriptase inhibitors combined with either a nonnucleoside reverse transcriptase inhibitor, a "boosted" protease inhibitor or integrase strand transfer inhibitors (INSTIs), which resulted in decreased HIV RNA levels (<50 copies/mL) at 48 weeks and CD4 cell increases in the majority of patients (Usach et al, 2013). Research indicates (McMahon et al, 2011) that despite HAART therapy, HIV infected individuals who are poor, homeless, hungry, or have less education, continue to have a higher risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has reported that W-1 is a 1-[(2-hydroxyethoxy)methyl]-6-(phenylthio)thymine in the NNRTI analogue class (Chen et al, 2012;Puig-de-la-Bellacasa et al, 2012), and this compound is able to inhibit viral replication by binding to the hydrophobic pocket within the polymerase active site of the p66 palm subunit ( Jonckheere et al, 2000;Zhan et al, 2013). In addition, different from its lead compound emivirine (Szczech et al, 2000;Yuasa et al, 1993) and other NNRTIs including nevirapine (Nikolenko et al, 2010;Silverthorn and Parsons, 2006;Usach et al, 2013), W-1 exhibited higher selectivity and more potent antiviral activity against NNRTI-resistant HIV-1 strains, probably owing to the substitution of halogen at the C5 position with a pyrimidine ring or on the C6 with an aromatic moiety Qin et al, 2010;Wang et al, 2012). Therefore, W-1 is a good candidate for further development as a prospective anti-HIV-1 resistance infection and treatment of acquired immunodeficiency syndrome.…”
mentioning
confidence: 94%